2024
DOI: 10.3390/nu16020244
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Serum Mineral Nutrients, Gut Microbiota, and Risk of Neurological, Psychiatric, and Metabolic Diseases: A Comprehensive Mendelian Randomization Study

Wang Li,
Bo-Min Lv,
Yuan Quan
et al.

Abstract: Recent observational studies have reported associations between serum mineral nutrient levels, gut microbiota composition, and neurological, psychiatric, and metabolic diseases. However, the causal effects of mineral nutrients on gut microbiota and their causal associations with diseases remain unclear and require further investigation. This study aimed to identify the associations between serum mineral nutrients, gut microbiota, and risk of neurological, psychiatric, and metabolic diseases using Mendelian ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Two MR studies found no association between circulating folate or vitamin C levels and the risk of MS. The discrepancy in results between nutrient supplementation and circulating nutrient levels could potentially be explained by the fact that nutrients may influence pathophysiological processes through other indirect pathways, such as affecting the gut microbiota ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two MR studies found no association between circulating folate or vitamin C levels and the risk of MS. The discrepancy in results between nutrient supplementation and circulating nutrient levels could potentially be explained by the fact that nutrients may influence pathophysiological processes through other indirect pathways, such as affecting the gut microbiota ( 48 ).…”
Section: Discussionmentioning
confidence: 99%